Analisis Evaluasi Kemampuan Lahan Pada Daerah Rentan Longsor Dengan Citra Satelit - Beny Harjadi (EnviroScienteae, 2020)
Watersheds that are bordered by hillsides and mountains often experience land degradation due to erosion and landslides. Areas with high erosion rates will cause marginal land. Starting from the problem of land experiencing land degradation, the purpose of this study is an analysis of the evaluation of land capability in areas prone to landslides. A combination of plants that are suitable for the LUC class and also for those that are resistant to landslides is needed. Determination of the LUC class in a watershed that is quite extensive requires analytical aids with satellite images that are relatively easy, fast, and accurate. Analysis of satellite images with SRTM radar images (Shuttle Radar Topography Mission) and Landsat TM 7+ images can analyze the LUC class. The results of the LUC analysis in the Banjarnegara watershed obtained the widest class of LUC IV 38.7% (4,940.6 ha) and the narrowest LUC VII for production forests was limited to 0.05% (6.4 ha), and no LUC class I (rice fields) and VIII (protected forest). Low LUC classes from LUC I, II, III, and IV are commonly used for agriculture (annual crops) and LUC V, VI, VII, and VIII for forestry plants (annual).